A Comparative Evaluation of Fracture Resistance of Three Post Systems and Their Mode of Failure: An In-Vitro Study - Manish Sundesha; Anita Choudhary; Priyanka Gubrellay; Eishita Negi; Harleen Chhina; Omni P. Jain; Nikita Patel (Journal of Pharmacy and Bioallied Sciences)
Aim: To analyze the fracture resistance of three post systems and their mechanism of failure. Materials and Procedures: Forty-five newly excised human mandibular single-rooted pre-molar, for periodontal or orthodontic reasons, were used. The teeth were separated into three groups (n = 15) based on the post system utilized. Group A had teeth restored with custom cast post; Group B had prefabricated glass fiber posts (Angelus post); and Group C with edelweiss composite post (Edelweiss Post). Results: The custom cast posts provided the highest fracture resistance but exhibited more unfavorable fractures. The edelweiss posts exhibited the least fracture resistance. Conclusion: Further investigations should be targeted at elucidating the force dynamics of this newer post system.